E-government: Implications on service provision. The case of Bulawayo City Council. - Siziva, Abigail (Midlands State University, 2017)
This Research is entitled E-Government- Implications on service provision. The Case of Bulawayo City Council. The researcher came up with objectives to guide the research which were to assess the extent to whether e-government is being used fully or partially used in BCC, to analyse the value added by the use of e-government in improving service provision, to examine the e-service delivery channels that Bulawayo City Council is using, to examine challenges associated with the use of e-government and to recommend strategies that can be used to improve the use of e-government. Bulawayo City Council started using e-government several years ago but it still faces challenges in providing efficient and effective services to the residents. In this regard it was imperative to find out through this research how the challenges faced in e-government can be minimised and the benefits maximised. Chapter two provides the literature review e-services that are provided by local authorities across the globe and the e-service stations that are used, the interrelationships in e-government, Challenges such as poor internet networks , lack of gadgets, resistance from residents, poor internal structures ,lack of ICT skills and lack of capital were highlighted. The quantitative and qualitative research designs were used, the quantitative meant to explain the what, where and when decision-making while the qualitative was to explain and represent the why and how in decision making to enable explaining of the aspects that cannot be expressed in numbers. The target population for the research was Bulawayo which has a population of 653 377 and covers 29 wards within its 5 districts. Sample groups comprised of councillors, residents and BCC employees. The sampling techniques used were Systematic Sampling, Stratified Random Sampling and Purposive Sampling. Primary data was collected using various data collection tools which are the questionnaires, interviews and observations. The researcher’s findings revealed that BCC has a few e-services that it is providing which are e-payments, e-billing, e-information and e-notifications. Bulawayo City Council delivers e-services through various stations like the website, call centre, SMS services. However e-government has not been fully rolled out in Bulawayo City Council and only a few services are available online while the majority are still being provided manually. The positive implications of e-government to service provision which include improved accessibility, improved quality, and increased security, reduced office congestion, reduced costs, reduced workloads and informed decision making were also discussed. The study revealed that in BCC e-government is there but it has not been fully rolled out as only a few e-services are provided and a few e-service stations are used due to various challenges afore mentioned. Therefore, the researcher came up with recommendations to help overcome the challenges so that BCC enjoys the positive implications that e-government can bring to service provision. This document therefore serves to highlight that e-government has the potential to improve the effectiveness and efficiency in service provision if it is well communicated to the end users and if the challenges are overcome.